Insurance symbiosis In Algeria and the reality of its application in light of Executive Decree 21-81 - Laouir, Ines; sahno, unokba (Journal of Social Sciences and Humanities, 2025)
The study aims to try to show what was stated in Executive Decree No. 21-81 and what was its impact on the Algerian insurance market as a gateway to enter the world of Takaful insurance and a new addition that gives the Algerian economy an outlet and a resource compatible with the provisions of Islamic law in order to complement the course of economic and financial policy pursued by the authorities guardian to open up to Islamic finance, and despite the late in addition to not addressing several elements such as those related to accounting and financial operations for the activity of Takaful insurance, but Economic operators hope through it to improve the Algerian market by allowing the establishment of companies and Takaful security windows that work to increase competitiveness, including improving the profitability and effectiveness of insurance companies that exist in the market or that will exist later in the hope that it will be the beginning of replacing the traditional insurance system with the Islamic Takaful insurance system.